INTEGRASI NILAI-NILAI ISLAM DALAM PEMBELAJARAN BAHASA INGGRIS DI MI AL-ISLAMIYAH BEBIDAS - Ahmad Sakrani (Al-mujahidah, 2023)
Abstract: One of the implications of the implementation of the 2013 curriculum at the Islamic orPublic Elementary School is in the unification of several general lesson contents in one theme. Thecombination automatically gives more distance or dichotomy between the content of generallessons with Islamic Education lesson. Thus, it needs competence called integration, which combine the content of general lessons with the spirit of Islamic values. This study aims to determine the level of integration of Islamic values in Inggris language learning at MI Al-Islamiyah Bebidas. A Qualitative Approach with a case study method was used where the data taken from interview, observation and document. It was found that the level of integration of Islamic values in Inggris language learning at MI Al-Islamiyah Bebidas included the philosophy, research method and approach, material, strategy and evaluation levels. The uniqueness of this school is its integration at the communication level. The level of integration in SDIT also needs to be supported by the knowledge and understanding of teachers about the worldview of the integration of Islam with comprehensive knowledge not only at the level of axiology and epistemology, but also ontology.